Defence transcriptome assembly and pathogenesis related gene family analysis in Pinus tecunumanii (low elevation) - Visser, Erik A. (BMC Genomics, 2018)
BACKGROUND: Fusarium circinatum is a pressing threat to the cultivation of many economically important pine tree species. Efforts to develop effective disease management strategies can be aided by investigating the molecular mechanisms involved in the host-pathogen interaction between F. circinatum and pine species. Pinus tecunumanii and Pinus patula are two closely related tropical pine species that differ widely in their resistance to F. circinatum challenge, being resistant and susceptible respectively, providing the potential for a useful pathosystem to investigate the molecular responses underlying resistance to F. circinatum. However, no genomic resources are available for P. tecunumanii. Pathogenesis-related proteins are classes of proteins that play important roles in plant-microbe interactions, e.g. chitinases; proteins that break down the major structural component of fungal cell walls. Generating a reference sequence for P. tecunumanii and characterizing pathogenesis related gene families in these two pine species is an important step towards unravelling the pine-F. circinatum interaction. RESULTS: Eight reference based and 12 de novo assembled transcriptomes were produced, for juvenile shoot tissue from both species. EvidentialGene pipeline redundancy reduction, expression filtering, protein clustering and taxonomic filtering produced a 50 Mb shoot transcriptome consisting of 28,621 contigs for P. tecunumanii and a 72 Mb shoot transcriptome consisting of 52,735 contigs for P. patula. Predicted protein sequences encoded by the assembled transcriptomes were clustered with reference proteomes from 92 other species to identify pathogenesis related gene families in P. patula, P. tecunumanii and other pine species. CONCLUSIONS: The P. tecunumanii transcriptome is the first gene catalogue for the species, representing an important resource for studying resistance to the pitch canker pathogen, F. circinatum. This study also constitutes, to our knowledge, the largest index of gymnosperm PR-genes to date. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-018-5015-0) contains supplementary material, which is available to authorized users.